2009
DOI: 10.1007/s00259-009-1224-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the performance of 18F-FDG PET in cutaneous melanoma

Abstract: FDG-PET is not useful in the evaluation of regional metastases, as it does not detect microscopic disease. However, FDG-PET could be useful in the detection of distant metastases, and could suggest its utility in the management of patients with cutaneous melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 42 publications
1
64
0
3
Order By: Relevance
“…Ultrasonography associated with Doppler evaluation is of choice in the monitoring of the regional basin, in as much as its sensibility in the detection of occult nodal metastases is approaching 90%; ultrasound utility is now being evaluated by the MSLT-II trial. On the other hand, PET/TC has a diagnostic accuracy superior to that of TC alone in the early detection of visceral metastases whilst its sensitivity in the evaluation of node metastases appears to be lower due to the fact that tumour deposits can be far below its detection threshold [34], [35] and [36]. Another controversial point is the impact of SLN features on OS.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography associated with Doppler evaluation is of choice in the monitoring of the regional basin, in as much as its sensibility in the detection of occult nodal metastases is approaching 90%; ultrasound utility is now being evaluated by the MSLT-II trial. On the other hand, PET/TC has a diagnostic accuracy superior to that of TC alone in the early detection of visceral metastases whilst its sensitivity in the evaluation of node metastases appears to be lower due to the fact that tumour deposits can be far below its detection threshold [34], [35] and [36]. Another controversial point is the impact of SLN features on OS.…”
Section: Discussionmentioning
confidence: 99%
“…It currently represents the state of the art in PET-based imaging. High-quality studies have shown that the diagnostic significance of PET and PET/CT in melanoma differs depending on tumor stage [104,132,133].…”
Section: S Reskementioning
confidence: 99%
“…The uptake of FDG is substantially increased in most types of cancers due to the increased metabolism of glucose by tumor cells, as is the case in most lung, colorectal, esophageal, stomach, head and neck, cervical, ovarian, and breast cancers, as well as melanoma and most types of lymphoma [1][2][3]. The utility of FDG in tumor imaging has been fully reviewed [4][5][6][7][8]. However, increased glucose uptake is not a tumor-specific phenomenon; it is also observed in normal cells, such as brain cells, heart cells, and brown fat [9], as well as in infection and inflammation [10].…”
Section: Metabolic Oncologic Tracersmentioning
confidence: 99%